Mast Cell Tumor in Dogs - Epidemiological and Clinical Aspects - Yamile Padilla Barreto, Monica; de Paiva, Felipe Noleto; Eugenio da Silva de Oliveira, Ciro; Souza Costa, Thiago; Sampaio Martins Land Manier, Bruna; Israel Fernandes, Julio (Acta Scientiae Veterinariae, 2025)
Background: Mast cell tumors (MCTs) are the most common malignant skin tumors in dogs, accounting for up to 22% of cutaneous neoplasms. They primarily affect elderly dogs, with no sex predisposition, although neutered dogs may be at higher risk. Certain breeds, such as Boxers, Labradors, and Pinschers, are more predisposed. Recognizing the biological variability of MCTs is essential for accurate diagnosis and appropriate treatment, especially through national studies. This study aimed to analyze the clinical characteristics of MCTs in patients treated at the veterinary oncology service of the Federal Rural University of Rio de Janeiro (UFRRJ), Brazil. Materials, Methods & Results: The study analyzed data from dogs with cutaneous mast cell tumors (MCTs) and other skin neoplasms, obtained from the database of the Veterinary Oncology Service at the Small Animal Veterinary Hospital (HVPA) -UFRRJ between 2011 and 2020. Information was collected on age, breed, sex, reproductive status, body condition, clinical signs, tumor progression, location, staging, and treatment. The control group included dogs with skin tumors other than MCTs. Statistical analysis involved descriptive statistics, the chi-square test, and univariate logistic regression to assess risk factors. Data processing was performed using MedCalc® and Statistix® software. During the study period, a total of 4072 new cases were attended, of which 847/4072 (20.8%) were cutaneous neoplasms, and 266/847 (31%) were diagnosed as MCTs, representing 6.5% of the total cases. Regarding body size, 99/266 (37.1%) were large-breed dogs, making up the largest group. In terms of breed, most patients were classified as mixed breed (98/266 - 36.8%), followed by Boxers (29/266 - 10.9%), Labradors (26/266 - 9.8%), and Pit Bulls (20/266 - 7.5%). Clinical data, including body condition score, clinical signs, macroscopic presentation, anatomical location, lymph node involvement, histopathological grade, presence of metastasis, staging, and treatment modalities, were also evaluated. Discussion: The study analyzed the incidence of cutaneous mast cell tumors (MCTs) in dogs, highlighting a higher frequency than previous studies, with 31.4% among skin tumors and 6.5% among all neoplasms diagnosed. This high prevalence may be related to increased owner awareness and advancements in veterinary diagnostics. The average age of affected dogs was 9 years, aligning with literature indicating a higher occurrence between 6 and 11 years. French Bulldogs developed MCTs earlier, between 4 and 6 years, possibly due to their shorter lifespan. No sex predisposition was identified, although some studies suggest a higher occurrence in males. The influence of neutering remains uncertain, but the data suggest a higher risk in neutered Labradors. Mixed-breed dogs were the most affected, followed by Boxers, a breed with a statistically higher predisposition. Pinschers showed an increased risk, despite previous studies not identifying a predisposition. Clinically, gastrointestinal signs were observed in 10.7% of cases. The trunk was the most commonly affected body region, and surgery was the primary treatment (37.6%), with adjuvant chemotherapy used in specific cases, primarily with the vinblastine and prednisone protocol. Chemotherapy was used as adjuvant treatment, and the most used protocol was the combination of vinblastine and prednisone as the protocol mentioned as first-line treatment in dogs with MCT. Keywords: neoplasia, mast cell tumor, canine, epidemiology. Título: Mastocitoma em cães - aspectos epidemiológicos e clínicos Descritores: neoplasia, mastocitoma, canino, epidemiologia.